A dependable and secure approach for secret key establishment and operation in automotive CPS - Giri, Naresh Kumar (Kansas State University, 2018)
Modern automobiles incorporate a network of electronic control units (ECUs) that provides a range of features such as safety, driver assistance, infotainment. Such network of ECUs in a vehicle are connected to each other through buses, forming interconnections called intra-vehicle network. Bus technologies that are widely used in modern day automobiles are controller area network (CAN), local interconnect network (LIN), and media oriented systems transport (MOST). These bus technologies, however, do not possess any security or dependability features, and thus are susceptible to vulnerabilities. Such vulnerabilities allow attackers to mount passive attacks (e.g., snooping) and/or active attacks (e.g., fault injection). In this study, we propose a scheme for secure authentication of automotive ECUs. Our proposed scheme ensures that only authenticated ECUs can participate in communication over the intra-vehicle network/bus. ECU authentication is carried out using certificate-based authentication which is implemented using elliptic curve cryptography (ECC). The study also proposes a symmetric (session) key-establishment mechanism within intra-vehicular network to establish a common symmetric (session) key for all ECUs to communicate over the network. The key-establishment mechanism removes the need of storing symmetric keys in ECU memory permanently. The study incorporates key refreshment by assigning a certain lifetime/timeframe period to symmetric (session) key and then regularly updates session key after the expiration of each lifetime. Our proposed method provides confidentiality and integrity in intra-vehicle ECU communication without violating safety and real-time constraints of the vehicle. Our approach leverages multi-core ECUs to provide fault-tolerance by using redundant multi-threading (FT-RMT), performs quick error detection (FT-QED) and accelerate performance using lightweight checkpointing (CP).
Keywords: Authentication; Symmetric key; Key generation; Key distribution